The relationships of resting-state brain entropy (BEN), ovarian hormones and behavioral inhibition and activation systems (BIS/BAS) - Donghui Song; Ze Wang (NeuroImage)
Brain entropy (BEN) quantifies irregularity, disorder and uncertainty of brain activity. Recent studies have linked BEN, derived from resting-state functional magnetic resonance imaging (rs-fMRI), to cognition, task activation, neuromodulation, and pharmacological interventions. However, it remains unknown whether BEN can reflect the effects of hormonal fluctuations. Furthermore, ovarian hormones are known to modulate behavioral traits, such as inhibitory control and impulsivity, as measured by the Behavioral Inhibition and Activation Systems (BIS/BAS). In this study, we investigated how ovarian hormones influence BEN and BIS/BAS in young adult women.The forty-four participants (mean age = 22.61 ± 2.14 years) were obtained from OpenNeuro in the study. Ovarian hormones including estradiol (E2), progesterone (PROG) and BIS/BAS were acquired before scanning. The voxel-wise BEN maps were calculated from the preprocessed rs-fMRI images. Pearson’s correlation and mediation analyses were used to assess the relationships between BEN and ovarian hormones as well as BIS/BAS.Our results revealed a negative correlation between BEN and PROG in frontoparietal network (FPN), including the dorsolateral prefrontal cortex (DLPFC) and posterior parietal cortex (PPC), as well as in the limbic network, encompassing the amygdala, hippocampus, and parahippocampal cortex. In contrast, BEN showed a positive correlation with impulsivity traits measured by the BAS-drive subscale of BAS in the left DLPFC. Additionally, PROG was negatively correlated with impulsivity traits measured by BAS-drive. Results from mediation analysis demonstrated that PROG reduces impulsivity, as measured by BAS-drive, by decreasing BEN in the left DLPFC and subsequently increasing functional connectivity (FC) within this region.These findings provide the first evidence that BEN reflects the influence of PROG on brain function and behavior. Furthermore, they elucidate the neural mechanisms through which PROG modulates impulsivity traits measured by BAS-drive: PROG enhances the temporal coherence (decreased entropy) of neural activity in the left DLPFC, which in turn increases temporal synchronization (increased FC) within this region during resting-state, and then enhances executive control functions, thereby negatively regulating impulsivity. These findings provide new insights into our understanding of the effects of ovarian hormones on the brain and behavior in women.